2008
DOI: 10.1177/0272989x08319958
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Diagnostic Accuracy and Safe Management in Difficult Diagnostic Problems in Family Medicine

Abstract: Supporting the gathering of critical information has the potential to improve the diagnosis and management of difficult problems in family medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…14 -16 In practice, the most common cognitive error is premature closure of the diagnostic process, in which the physician may not even consider the correct diagnosis as a possibility. [17][18][19][20] For example, in a study of 583 diagnostic errors, Schiff and colleagues 18 found that "failure or delay in considering the diagnosis" was the most common failure in the diagnostic process. The most commonly missed diagnoses-cancer, pulmonary embolus, coronary disease, aneurysms, appendicitis-have been docu-mented in previous studies, 8,18,21,22 but little is known about the presenting complaints or initial (incorrect) diagnoses that precede these missed diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…14 -16 In practice, the most common cognitive error is premature closure of the diagnostic process, in which the physician may not even consider the correct diagnosis as a possibility. [17][18][19][20] For example, in a study of 583 diagnostic errors, Schiff and colleagues 18 found that "failure or delay in considering the diagnosis" was the most common failure in the diagnostic process. The most commonly missed diagnoses-cancer, pulmonary embolus, coronary disease, aneurysms, appendicitis-have been docu-mented in previous studies, 8,18,21,22 but little is known about the presenting complaints or initial (incorrect) diagnoses that precede these missed diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Kostopoulou and colleagues presented 84 family doctors with seven difficult computer-based diagnostic scenarios for which they could seek further information for diagnosis and management. Scoring criteria developed from literature and expert opinion showed that inappropriate management that could have been potentially harmful was planned in 78% of incorrectly diagnosed cases [7]. While this suggests that achieving a correct diagnosis is essential for safe patient care, the reality is that clinicians are often faced with presentations that require treatment when the diagnosis is uncertain or at best a guess.…”
Section: The Influence Of Case Management On Diagnostic Accuracymentioning
confidence: 99%
“…a set or sequence of actions to attain a diagnosis) into distinct stages [7,10,11]. Schiff et al [11] used the DEER taxonomy tool across 669 cases which involved 310 clinicians.…”
Section: Understanding Decision Making During the Diagnostic Process:mentioning
confidence: 99%
See 1 more Smart Citation
“…However, I wonder whether this time limitation could potentially impact on the ability of primary care practitioner's to make complex diagnoses early, a potential 'achilles heel' of general practice, 2 thus adding to diagnostic delay and error, the biggest cause of medicolegal claims against GPs. 3 Recent research has shown that health systems with a gatekeeper function have lower cancer 1-year survival. 4 Around 23% of patients consult three or more times with a GP before suspected cancer referral, with increased repeat consultations in those from ethnic minorities and for certain cancers before referral.…”
Section: The Bjgpmentioning
confidence: 99%